2004
DOI: 10.1116/1.1783320
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of oxide during prolonged anodization of aluminum in preparing ordered nanopore arrays

Abstract: Ideally ordered 10 nm channel arrays grown by anodization of focused-ion-beam patterned aluminum Time and orientation dependence of ordering in anodized aluminum for self-organized magnetic arraysIn this study, one-step anodization was conducted on both mechanically polished and electropolished Al foils at different temperatures to examine their growth characteristics during prolonged anodization. Several unusual phenomena different from those reported previously were observed, especially for the preparation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Next, the influence of these operating conditions in the process is particularly analyzed at 10 mA cm À2 , a current density which remains in the upper limit of mild anodizing without attaining hard anodizing conditions. The current density is also higher to that registered in anodizing at constant voltage in oxalic acid at 40 V (usually smaller than 7 mA cm À2 ), obtaining higher growth rates due to optimization of operating conditions [12,37,43].…”
Section: Setting a Self-ordered Anodizing At Constant Currentmentioning
confidence: 91%
See 1 more Smart Citation
“…Next, the influence of these operating conditions in the process is particularly analyzed at 10 mA cm À2 , a current density which remains in the upper limit of mild anodizing without attaining hard anodizing conditions. The current density is also higher to that registered in anodizing at constant voltage in oxalic acid at 40 V (usually smaller than 7 mA cm À2 ), obtaining higher growth rates due to optimization of operating conditions [12,37,43].…”
Section: Setting a Self-ordered Anodizing At Constant Currentmentioning
confidence: 91%
“…In recent decades, it has been established that high-quality nanomaterials are obtained by this method only if pores are well defined and homogeneous. For this reason, the degree of ordering of these cell arrangements plays an important role in the homogeneity of the resulting nanomaterials and researchers have tried hard to understand and control this phenomenon [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the morphological parameters of the nanostructured AAO, such as the degree of arrangement of the porous structure, the pore diameter, the interpore distance, the pore density, the film thickness, and the porosity, strongly depend on the variables of the synthesis, such as nature, concentration, and temperature of the electrolyte, together with the applied voltage and the anodization time [7][8][9][10][11]. Likewise, the purity of the aluminium used as substrate and the applied surface pretreatment to homogenize the surface have directly affected the ordering degree of the nanoporous arrangement [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…where a Al and a 3 . Therefore, the thermal stress effect from the temperature increase can be ignored.…”
Section: B Mechanical Stress Fieldmentioning
confidence: 99%
“…The anodization process and pore pattern periodicity are sensitive to applied voltage, current density, temperature, and pH value of the electrolyte. [1][2][3][4] Efforts have been devoted to creating regular pore arrays through guiding patterns formed before the anodization. One example is creating shallow strips, spots, or both kinds of features on the metal surface before the anodization from different electropolishing conditions.…”
Section: Introductionmentioning
confidence: 99%